The right to be forgotten and other reasons for re-cataloging audiovisual archives - López-de-Quintanta-Sáenz, Eugenio (Anuario ThinkEPI, 2015)
Without metadata, the value of the stock shots archived as audiovisual heritage decreases due to the limitations of content retrieval. A number of archives are not catalogued yet, and others have a metadata structure but need to be re-catalogued and re-indexed. Incomplete metadata, legal issues related to the right to be forgotten, new relevance of events or people, or new journalistic approaches to the information are some of the triggers of this requirement, which is extremely complex and sometimes unviable. This leads us to assume that there are certain unachievable limitations on audiovisual archives management.
Keywords: Audiovisual archive; Television archives; Information management; Metadata; Cataloguing; Indexing; Recataloguing; Reindexing; Right to be forgotten; Limitations.